Иноязычные ресурсы современного украинского словообразования - Karpilovska, Evgenija (Slavia Centralis, 2020)
Foreign-language resources of contemporary Ukrainian word formation The paper discusses the problem of the use of borrowed resources in modern Ukrainian derivation. Analysis of the new Ukrainian words was done in relation to the nominations of the same concepts in other Slavic languages. Material research proves that the influence of donorlanguages, and, above all, English as the leading language of globalization on contemporary Ukrainian derivation, can be explicit vs. hidden, primary vs. secondary. The functional potential of nominations with foreign-language resources enables one to judge about nominative and communicative importance of an innovation and to predict their fate in the recipient-language.